2017
DOI: 10.7567/jjap.57.0102bg
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxicity of carbon black nanoparticles synthesized from solution plasma on human lung fibroblast cells

Abstract: Carbon black nanoparticles (CB-NPs) have been synthesized from liquid benzene by a solution plasma method at room temperature and atmospheric pressure. The morphological observation by scanning electron microscopy revealed the agglomeration of aggregated fine particles. The synthesized CB-NPs were predominantly amorphous as confirmed by X-ray diffraction. The in vitro cytotoxicity of CB-NPs on the human lung fibroblast (MRC-5) cell line was assessed by the 3-(4,5-dimethylthiazole-2-yl)-2,5-diphenyltetrazolium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, the emissions of C 2 swan band (440 nm) and • CH (431 nm) could be observed in the solution with ethanol, due to the dissociation of ethanol vapor. This evidence shows benefit in the synthesis of carbon nanomaterials via the solution plasma process, similar to the systems with other organic solvents [ 27 , 62 ]. According to the evidence previously showed, it pointed out that the choice of solutions, which include conductivity, pH, and type of ions, exhibits a significant effect on the properties of plasmas in liquids.…”
Section: Solution Plasma Process (Spp): Chemistry and Influencing Parametersmentioning
confidence: 88%
“…However, the emissions of C 2 swan band (440 nm) and • CH (431 nm) could be observed in the solution with ethanol, due to the dissociation of ethanol vapor. This evidence shows benefit in the synthesis of carbon nanomaterials via the solution plasma process, similar to the systems with other organic solvents [ 27 , 62 ]. According to the evidence previously showed, it pointed out that the choice of solutions, which include conductivity, pH, and type of ions, exhibits a significant effect on the properties of plasmas in liquids.…”
Section: Solution Plasma Process (Spp): Chemistry and Influencing Parametersmentioning
confidence: 88%
“…However, carbon black has already been used for biocompatible strain sensors and flexible bioelectrodes, [50,51] and the one used in this study showed high cell viability (100%) at a concentration of 32.5 µg mL −1 during an in vitro cytotoxicity study. [52] Additionally, as there is no evidence that the CSMP composite is nontoxic, an in vitro cytotoxicity test was performed (according to ISO 10993-5:2009 Biological Evaluation of Medical Devices -Part 5). The results showed the cytocompatibility of the material for at least 284 min, the maximum time duration of a cardiac ablation procedure (Document S1, Supporting Information).…”
Section: Fabrication Methodsmentioning
confidence: 99%
“…This approach offers several advantages, including a simple process, short synthesis time, operation at atmospheric pressure and room temperature, and low energy and chemical consumptions . So far, SP has been applied to synthesizing numerous materials, such as heteroatom-doped carbon, metal/carbon composite, amino-modified carbon, and metal nanoparticles. However, so far, SP does not appear to have been applied to the simultaneous synthesis and surface modification of metal/carbon catalysts.…”
Section: Introductionmentioning
confidence: 99%